Assay development and high-throughput screening for small molecule inhibitors of a Vibrio cholerae stress response pathway - Stanbery L; Matson JS (Dove Medical Press, 2017)
Laura Stanbery, Jyl S Matson Department of Medical Microbiology and Immunology, College of Medicine and Life Sciences, The University of Toledo, Toledo, OH, USA Abstract: Antibiotics are important adjuncts to oral rehydration therapy in cholera disease management. However, due to the rapid emergence of resistance to the antibiotics used to treat cholera, therapeutic options are becoming limited. Therefore, there is a critical need to develop additional therapeutics to aid in the treatment of cholera. Previous studies showed that the extracytoplasmic stress response (σE) pathway of Vibrio cholerae is required for full virulence of the organism. The pathway is also required for bacterial growth in the presence of ethanol. Therefore, we exploited this ethanol sensitivity phenotype in order to develop a screen for inhibitors of the pathway, with the aim of also inhibiting virulence of the pathogen. Here we describe the optimization and implementation of our high-throughput screening strategy. From a primary screen of over 100,000 compounds, we have identified seven compounds that validated the growth phenotypes from the primary and counterscreens. These compounds have the potential to be developed into therapeutic agents for cholera and will also be valuable probes for uncovering basic molecular mechanisms of an important cause of diarrheal disease. Keywords: Vibrio cholerae, stress response, σE, high-throughput screening